Interfacial bonding mechanism in Al/coated steel dissimilar refill friction stir spot welds. Issue 6 (June 2019) - Shen, Z.; Ding, Y.; Chen, J.; Amirkhiz, B. Shalch; Wen, J.Z.; Fu, L.; Gerlich, A.P.
Abstract: Defect-free dissimilar Al/zinc coated steel and Al/AlSi coated steel welds were successfully fabricated by refill friction stir spot welding. However, Al alloy and uncoated steel could not be welded under the same welding condition. Al-Zn eutectic layer formed at the Al/zinc coated steel interface showed non-uniformity in thickness and nanoscale intermetallic (IMC) produced was discontinuous. The bonding formation between the Al-Zn layer and the surrounding materials was attributed to a liquid/solid reaction mechanism. Bonding formation at Al alloy and AlSi coated steel interface was attributed to a solid/solid reaction mechanism, as the joining process did not involve with melting of base metals or AlSi coating materials. Kissing bond formed at the weld boundary acted as a crack initiation and propagation site, and the present study showed that weld strength of Al 5754/AlSi coated steel was greatly influenced by properties of original IMC layer.